Extruded Wheat Bran Consumption Increases Serum Short-Chain Fatty Acids but Does Not Modulate Psychobiological Functions in Healthy Men: A Randomized, Placebo-Controlled Trial - Dalile, Boushra; La Torre, Danique; Kalc, Polona; Zoppas, Francesca; Roye, Chiara; Loret, Chrystel; Lamothe, Lisa; Bergonzelli, Gabriela; Courtin, Christophe M.; Vervliet, Bram; Oudenhove, Lukas Van; Verbeke, Kristin (Frontiers in Nutrition, 2022)
Background: Incorporation of wheat bran (WB) into food products increases intake of dietary fiber, which has been associated with improved mood and cognition and lower risk for psychiatric disorders such as depression, with short-chain fatty acids (SCFAs) as candidate mediators of these effects. Modifying WB using extrusion cooking increases SCFA production in vitro relative to unmodified WB. Objective: The effects of extruded WB on psychobiological functioning and the mediating role of SCFAs herein were evaluated. Methods: In a randomized, triple-blind, placebo-controlled trial, 69 healthy male participants consumed 55 g of breakfast cereal containing either extruded WB or placebo daily for 28 days. At pre- and post-intervention visits, the cortisol response to experimentally induced stress was measured as a primary outcome. In addition, serum SCFAs and brain-derived neurotrophic factor were quantified as potential mediators. Secondary psychobiological outcomes included subjective stress responses, responses to experimentally induced fear, cortisol awakening response, heart rate variability, and retrospective subjective mood ratings. Intestinal permeability, fecal SCFAs, and stool consistency were measured as secondary biological outcomes. Results: Extruded WB increased serum acetate and butyrate (p < 0.05). None of the primary or secondary outcomes were affected by the intervention. Participants who consumed placebo exhibited an increase in percentage of fecal dry weight but did not report increased constipation. Despite these statistically significant effects, these changes were small in magnitude. Conclusions: Extruded WB consumption increased serum short-chain fatty acids but did not modulate psychobiological functions in healthy men. Effective modulation of psychobiological functions may require greater increases in SCFAs than those achieved following extruded WB consumption. Rather than attempting to induce health benefits with a single fiber-rich food, combinations of different fibers, particularly highly fermentable ones, might be needed to further increase SCFA production and uptake in the systemic circulation to observe an effect on psychobiological processes.